Protective Effect of Alpha-Tocopherol Isomer from Vitamin E against the H2O2 Induced Toxicity on Dental Pulp Cells - Vargas, Fernanda da Silveira [UNESP]; Soares, Diana Gabriela [UNESP]; Dias Ribeiro, Ana Paula; Hebling, Josimeri [UNESP]; De Souza Costa, Carlos Alberto [UNESP] (Hindawi Publishing Corporation, 2014)
The aim of this study was to evaluate the protective effects of different concentrations of vitamin E alpha-tocopherol (alpha-T) isomer against the toxicity of hydrogen peroxide (H2O2) on dental pulp cells. The cells (MDPC-23) were seeded in 96-well plates for 72 hours, followed by treatment with 1, 3, 5, or 10 mM alpha-T for 60 minutes. They were then exposed or not to H2O2 for 30 minutes. In positive and negative control groups, the cells were exposed to culture medium with or without H2O2 (0.018%), respectively. Cell viability was evaluated by MTT assay (Kruskal-Wallis and Mann-Whitney tests; alpha = 5%). Significant reduction of cell viability (58.5%) was observed in positive control compared with the negative control. Cells pretreated with alpha-T at 1, 3, 5, and 10 mM concentrations and exposed to H2O2 had their viability decreased by 43%, 32%, 25%, and 27.5%, respectively. These values were significantly lower than those observed in the positive control, thereby showing a protective effect of alpha-T against the H2O2 toxicity. Overall, the vitamin E alpha-T isomer protected the immortalized MDPC-23 pulp cells against the toxic effects of H2O2. The most effective cell protection was provided by 5 and 10 mM concentrations of alpha-T.